Islands of Good Government: Explaining Successful Corruption Control in Two Spanish Cities - Drápalová, Eliška (2020)
Between 2012 and 2018, Spanish public opinion has been shaken by a seemingly endless series of corruption scandals, to the point that corruption has become one of the main long-term concerns of the Spanish population, according to nation-wide surveys. Despite the sharp rise in corruption scandals within local authorities, there are Spanish cities that have managed to limit corruption and build a transparent and efficient government, which stand out as islands of integrity and good governance. This article qualitatively investigates two cities in Spain—Alcobendas and Sant Cugat del Vallès—which, despite being in a region with comparatively lower quality of government, have managed to successfully control corruption. We argue that the key to success is the administrative reorganization prompted by the appointment of city managers that institutionalized professional management. Findings also have implications for practitioners, meaning that complex anti-corruption legislative frameworks will not work within an overburdened administration unless the administrative structure is reformed.